2014
DOI: 10.1093/fampra/cmu031
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with adherence to glaucoma pharmacotherapy in the primary care setting

Abstract: Background.Primary open-angle glaucoma is a leading cause of irreversible blindness.Objectives.To identify factors associated with adherence to glaucoma pharmacotherapy in the primary care setting, focusing on physicians’ role.Methods.Patients were recruited from primary care clinics and telephone-interviewed using a structured questionnaire that addressed patient-, medication-, environment- and physicians-related factors. Patients’ data on pharmacy claims were retrieved to calculate the medication possession … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
41
6
11

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 21 publications
6
41
6
11
Order By: Relevance
“…Moreover, duration of prescription was available for each purchase, obviating the need to approximate the expected refill date according to the various glaucoma eye drops and bottle volumes. 27 In conclusion, our findings support previous recommendations 12 to improve adherence among glaucoma patients, particularly among younger male patients and patients at earlier stages of the disease. This could be done by educational programs 28 to increase awareness, regular physician visits, and communicating with patients (or their caregivers) the importance of adherence for preventing glaucoma damage.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Moreover, duration of prescription was available for each purchase, obviating the need to approximate the expected refill date according to the various glaucoma eye drops and bottle volumes. 27 In conclusion, our findings support previous recommendations 12 to improve adherence among glaucoma patients, particularly among younger male patients and patients at earlier stages of the disease. This could be done by educational programs 28 to increase awareness, regular physician visits, and communicating with patients (or their caregivers) the importance of adherence for preventing glaucoma damage.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to previous international studies, adherence with glaucoma therapy was particularly low among males, 18 patients under 70, 19,20 as well as individuals belonging to lower socioeconomic status. 12,20,21 In contrast, being seen by a female ophthalmologist, higher IOP at baseline, and a more aggressive type presentation of glaucoma (eg, exfoliation) were more likely to be adherent with therapy. Interestingly, patients who were treated mainly by glaucoma specialists have similar adherence to those who were treated by general ophthalmologists.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Age was not a cause of nonadherence in their patients. However, other studies showed that some demographic variables such as sex and marital status did not significantly influence medication adherence …”
Section: Discussionmentioning
confidence: 90%
“…Hyperemia, pain, burning, and ocular discomfort are common causes of patient nonadherence [11]. On the other hand, patient-related, medicationrelated, physician-related and environmental, psychological and socioeconomical factors has been reported as important reasons for therapy adherence [12,13].…”
Section: Discussionmentioning
confidence: 99%